2021
DOI: 10.1093/bioinformatics/btab737
|View full text |Cite
|
Sign up to set email alerts
|

DeepTrio: a ternary prediction system for protein–protein interaction using mask multiple parallel convolutional neural networks

Abstract: Motivation Protein-protein interaction (PPI), as a relative property, is determined by two binding proteins, which brings a great challenge to design an expert model with an unbiased learning architecture and a superior generalization performance. Additionally, few efforts have been made to allow PPI predictors to discriminate between relative properties and intrinsic properties. Results We present a sequence-based approach, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 41 publications
0
47
0
Order By: Relevance
“…Recent investigations have shown that many researchers use a convolutional network or graph convolutional neural network [ 50 ] combined with the 3D structure information of proteins to solve the problem of PPI prediction [ 51 ]. In the model evaluation, these methods have achieved good results.…”
Section: Resultsmentioning
confidence: 99%
“…Recent investigations have shown that many researchers use a convolutional network or graph convolutional neural network [ 50 ] combined with the 3D structure information of proteins to solve the problem of PPI prediction [ 51 ]. In the model evaluation, these methods have achieved good results.…”
Section: Resultsmentioning
confidence: 99%
“…The protein representations are generated by retrieving the amino acid embeddings according to the indices provided by input sequences. NXTfusion [68] and DeepTrio [40] use this method to learn the protein representations for model input.…”
Section: Deep Learning Methodologymentioning
confidence: 99%
“…It is better for PPI prediction models to ensure a consistent prediction from arbitrarily ordered inputs(the featurization should be symmetric). Based on the above principle, the Siamese architecture [33] , [34] , [40] is usually employed, which contains two identical submodules sharing the same configuration and weights. In this section, we mainly describe the learning architectures adopted in the recently proposed deep learning methods for PPI prediction.…”
Section: Deep Learning Methodologymentioning
confidence: 99%
See 2 more Smart Citations